2013
DOI: 10.1128/jb.00669-13
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Concentration and the Putative Sensor Kinase Protein CckA Modulate Cell Lysis and Release of the Rhodobacter capsulatus Gene Transfer Agent

Abstract: The gene transfer agent of Rhodobacter capsulatus (RcGTA) is a bacteriophage-like genetic element with the sole known function of horizontal gene transfer. Homologues of RcGTA genes are present in many members of the alphaproteobacteria and may serve an important role in microbial evolution. Transcription of RcGTA genes is induced as cultures enter the stationary phase; however, little is known about cis-active sequences. In this work, we identify the promoter of the first gene in the RcGTA structural gene clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 53 publications
(96 reference statements)
1
66
0
Order By: Relevance
“…Transcription of these lysis genes was shown to be regulated by the histidine sensor kinase CckA. Evidently, a holin-endolysin system, not recognized in the early studies by Lang and Beatty, mediates GTA release from this alphaproteobacterium (60). It is likely that this mechanism generally provides the means for GTA release.…”
Section: Involvement Of Holins In Bacterial Gene Transfermentioning
confidence: 97%
See 1 more Smart Citation
“…Transcription of these lysis genes was shown to be regulated by the histidine sensor kinase CckA. Evidently, a holin-endolysin system, not recognized in the early studies by Lang and Beatty, mediates GTA release from this alphaproteobacterium (60). It is likely that this mechanism generally provides the means for GTA release.…”
Section: Involvement Of Holins In Bacterial Gene Transfermentioning
confidence: 97%
“…Westbye et al (60) identified the promoter of the first gene in this GTA gene cluster and showed that gene transfer frequencies depend on the growth medium. Surprisingly, millimolar concentrations of phosphate posttranslationally inhibited the lysis-dependent release of GTA from the cells.…”
Section: Involvement Of Holins In Bacterial Gene Transfermentioning
confidence: 99%
“…R. capsulatus strains lacking the unlinked cckA, chpT, or ctrA genes are unable to act as transduction donors either because RcGTA structural gene transcripts are not induced (ctrA mutants) or because maturation and release of RcGTA are impaired (cckA and chpT mutants). It appears that nonphosphorylated CtrA is needed for expression of RcGTA structural genes early in the induction process and that phosphorylated CtrA (CtrAϳP) is needed late in the induction process for cell lysis and release of RcGTA particles (4,11,12). Furthermore, cells lacking the ctrA gene are unable to act as recipients in RcGTA-mediated gene transfer, because the CtrA protein …”
mentioning
confidence: 99%
“…In the stationary phase of R. capsulatus cultures, a subset (Ͻ1%) of the cell population produces RcGTA particles that resemble a tailed bacteriophage. Essentially random ϳ4-kb fragments of genomic DNA are packaged into the RcGTA particles, and particles are released by cell lysis mediated by a canonical endolysin/holin system, as for bacteriophage release (2)(3)(4). RcGTA particles recognize a capsular polysaccharide receptor on R. capsulatus cells using spikes located on the RcGTA capsid (5).…”
mentioning
confidence: 99%
“…The RcGTA primary structural gene cluster consists of an ϳ15-kb region of the chromosome, and additional essential factors, including a holin and endolysin, are encoded in distant genome regions (5,7,9). Production of RcGTA requires the CtrA response regulator, and transcription is modulated by the GtaI/R quorumsensing system (10)(11)(12).…”
mentioning
confidence: 99%